Genomic correlates of response to immune checkpoint therapies in clear cell renal cell carcinoma - Miao, Diana (Science, 2018)
Immune checkpoint inhibitors targeting the programmed cell death-1 receptor (PD-1) improve survival in a subset of patients with clear cell renal cell carcinoma (ccRCC). To identify genomic alterations in ccRCC that correlate with response to anti-PD-1 monotherapy, we performed whole exome sequencing of metastatic ccRCC from 35 patients. We found that clinical benefit was associated with loss-of-function mutations in the PBRM1 gene (p=0.012), which encodes a subunit of a SWI/SNF chromatin remodeling complex (the PBAF subtype). We confirmed this finding in an independent validation cohort of 63 ccRCC patients treated with PD-(L)1 blockade therapy alone or in combination with anti-CTLA-4 therapies (p=0.0071). Gene expression analysis of PBAF-deficient ccRCC cell lines and PBRM1-deficient tumors revealed altered transcriptional output in JAK/STAT, hypoxia, and immune signaling pathways. PBRM1 loss in ccRCC may alter global tumor cell expression profiles to influence responsiveness to immune checkpoint therapy.